The Effects of Temperature and Culture Medium Composition on Protein Recombinant JSU-pET Expression - Indriawati Indriawati; Slamet Diah Volkandari; Endang Tri Margawati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2019)
There are several factors influencing the protein expression. The study was aimed to increase the yield of protein recombinant JSU-pET by applying combination of temperature and medium culture composition. This research was composed in a 2x2 factorial design with two level temperatures of 37oC and 25oC and 2 medium compositions of LB and mLB (modified). Escherichia coli bearing JSU-pET plasmid were grown in two applied media and incubated in two applied temperatures. The cells were harvested by centrifugation the pellets were then lysed. The lysed cells were centrifuged, the supernatant then purified by Ni-NTA Resin Agarose. The purified JSU protein recombinant was characterized and quantified by spectrophotometer. The Result showed that the JSU protein recombinant was successfully expressed on the right size (37kDa) in all treatments even though the JSU-pET showed sharper band in m LB at 37oC. Statistically the protein yield was not significant different (P>0.05), however culture temperature of 25oC showed higher yield (0.618±0.095 vs 0.704±0.094) than cultured at 37oC (0.598±0.137 vs 0.553±0.041), respectively either cultured in LB or mLB. This finding suggests that a lower culture temperature could increase protein yield both either in LB or modified LB.